2021
DOI: 10.3390/cosmetics8010017
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behaviour of Real-Time Sensor for Determination Mercury in Cosmetic Products Based on PANI/MWCNTs/AuNPs/ITO

Abstract: Mercury is a common ingredient found in skin lightening soaps, creams, and makeup-cleansing products. It may cause skin rashes, skin discolouration, and scarring, as well as a reduction in the skin’s resistance to bacterial and fungal infections. By looking at this scenario, developing a sensor that involved a simple procedure and fasts for real-time detection without affecting mercury sensitivity is urgently needed. For that reason, a fast and sensitive electrochemical method was developed to determine mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Most of the voltammetric sensors use anodic stripping voltammetry, which allows detection at lower concentrations owing to the pre-concentration; thus, the detection limit obtained in this work is not as low. Nevertheless, the detection limit achieved here was much lower than that in [ 43 , 44 ], which also used preconcentration. Furthermore, the sensor developed by us has the advantage of a simpler platform than in [ 9 , 27 , 44 ].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Most of the voltammetric sensors use anodic stripping voltammetry, which allows detection at lower concentrations owing to the pre-concentration; thus, the detection limit obtained in this work is not as low. Nevertheless, the detection limit achieved here was much lower than that in [ 43 , 44 ], which also used preconcentration. Furthermore, the sensor developed by us has the advantage of a simpler platform than in [ 9 , 27 , 44 ].…”
Section: Resultsmentioning
confidence: 62%
“…Nevertheless, the detection limit achieved here was much lower than that in [ 43 , 44 ], which also used preconcentration. Furthermore, the sensor developed by us has the advantage of a simpler platform than in [ 9 , 27 , 44 ]. On the other hand, only two sensors used fixed potential techniques for mercury measurement and their architecture does not include carbon nanotubes or ionophores.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Also, a recent study reported the synthesis of PANI/MWCNT/AuNP composites for electrochemical detection of mercury in cosmetic products using methylene blue as a redox indicator. 200…”
Section: Multiwalled Carbon Nanotube–gold Nanoparticle Composites (Mw...mentioning
confidence: 99%